2020
DOI: 10.3390/app10217800
|View full text |Cite
|
Sign up to set email alerts
|

Automated Code-Smell Detection in Microservices Through Static Analysis: A Case Study

Abstract: Microservice Architecture (MSA) is becoming the predominant direction of new cloud-based applications. There are many advantages to using microservices, but also downsides to using a more complex architecture than a typical monolithic enterprise application. Beyond the normal poor coding practices and code smells of a typical application, microservice-specific code smells are difficult to discover within a distributed application setup. There are many static code analysis tools for monolithic applications, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The authors validated their works on five open-source projects and further discussed the roadmap for implementing the next set of smells. A similar study was conducted by Walker et al [27,28] where the authors identified 11 microservice-specific code smells using static analysis. They also used several adjustable threshold values to change the flexibility of pattern matching.…”
Section: Pattern-based Analysismentioning
confidence: 89%
See 4 more Smart Citations
“…The authors validated their works on five open-source projects and further discussed the roadmap for implementing the next set of smells. A similar study was conducted by Walker et al [27,28] where the authors identified 11 microservice-specific code smells using static analysis. They also used several adjustable threshold values to change the flexibility of pattern matching.…”
Section: Pattern-based Analysismentioning
confidence: 89%
“…Most papers that used static analysis as their main method tended to do so to gather information specifically about the architecture. These techniques depend on analyzing statically defined artifacts to reconstruct an architectural view of a system, mainly analyzing source code [16,26,28,30], but also other artifacts, such as OpenAPI specifications [15]. Static analysis is applicable to other goals as well, such as anti-pattern or code smell detection [26,28,29].…”
Section: Rq1: Methods and Techniques Usedmentioning
confidence: 99%
See 3 more Smart Citations